Online Loans: Legal Aspects in the Era of Financial Technology - Rachman, Rahmia (Fakultas Hukum Universitas Widya Mataram, 2024)
The presence of financial technology carries a very high risk due to the minimal information provided by business actors, such as the amount of interest and administrative fees. The purpose of this research is to understand the form of legal protection for debtors in online loan agreements based on financial technology and to determine the role of the Financial Services Authority in overseeing the proliferation of financial technology services. The method used in this research is normative legal research. The results of this study are preventive protection of debtors by applying the basic principles of legal protection for service users, as well as repressive legal protection, namely Fintech service providers must be responsible for consumer losses arising from errors and omissions. The role of the Financial Services Authority includes the authority to regulate, supervise and protect consumers and deploy the Investment Task Force